Acute Psychosis as Major Clinical Presentation of Legionnaires' Disease. (28th July 2016) - Coentre, Ricardo; Silva-dos-Santos, Amílcar; Talina, Miguel Cotrim
Abstract : We report a case of a 61-year-old woman who presented with acute psychosis as a major manifestation of Legionnaires' disease in the absence of other neuropsychiatric symptoms. Clinical history revealed dry cough and nausea. Observation showed fever and auscultation crackles in the lower lobe of the right lung. Laboratory testing demonstrated elevated C-reactive protein and lung chest radiograph showed patchy peribronchial and right lower lobe consolidation. Soon after admission, she started producing purulent sputum. Epidemiological data suggested Legionella pneumophila as possible cause of the clinical picture that was confirmed by urinary antigen detection and polymerase chain reaction of the sputum. She was treated with levofloxacin 750 mg/day for 10 days with complete remission of pulmonary and psychiatric symptoms. She has not had further psychotic symptoms.